Analyzing banking risk : a framework for assessing corporate governance and risk management - Greuning, Hennie van (World Bank e-Library., 2009)
The third edition of 'Analyzing Banking Risk' provides a comprehensive overview of topics dealing with the assessment, analysis, and management of financial risks in banking. The publication emphasizes risk-management principles and stresses that key players in the corporate governance process are accountable for managing the different dimensions of financial risk. This third edition remains faithful to the objectives of the original publication. A significant new addition is the inclusion of chapters on the management of the treasury function. Advances made by the Basel Committee on Banking Sup.